1997
DOI: 10.1007/bf01623693
|View full text |Cite
|
Sign up to set email alerts
|

Initiation of hormone replacement therapy after diagnosis of osteoporosis by bone densitometry

Abstract: The effect of osteoporosis, as diagnosed by bone densitometry, on general practitioners' decisions to initiate hormone replacement therapy (HRT) was assessed. Data for the study were collected by questionnaire from 147 women (> 40 years), previously referred for measurement of bone mineral density (BMD) at the proximal forearm. Among the women, at the time of BMD measurement, current and ever use of HRT was 35% and 50% respectively, and 25.2% were osteoporotic on the basis of their BMD level. HRT was more like… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 8 publications
1
2
0
Order By: Relevance
“…Our findings on BMD T-scores are consistent with several other studies [911, 13, 14, 16, 19]. However, previous studies looking at the association between BMD T-scores and treatment have used prospective data sources.…”
Section: Discussionsupporting
confidence: 92%
“…Our findings on BMD T-scores are consistent with several other studies [911, 13, 14, 16, 19]. However, previous studies looking at the association between BMD T-scores and treatment have used prospective data sources.…”
Section: Discussionsupporting
confidence: 92%
“…A BMD test may help clarify the benefit‐to‐risk ratio for those women who are uncertain about initiating drug therapy. A number of studies have found that knowing the result of a BMD test influences drug prescribing and also lifestyle changes (34–41) . In these studies, women were between 3 and 16 times more likely to start or receive a prescription for hormone replacement therapy if the BMD report classified the patient as having low bone mass or osteoporosis.…”
Section: Discussionmentioning
confidence: 99%
“…This observation suggests that ibandronate treatment is more effective in subjects with more serious conditions of osteoporosis and that ibandronate is useful for long-term use. However, there can be a potential selection bias in the trials’ recruitment phase of the included studies as many other studies have reported a positive relationship between the start of any treatment for osteoporosis and T scores [ 62 65 ]. Moreover, diagnosis and treatment rates of osteoporosis are quite low [ 66 , 67 ].…”
Section: Discussionmentioning
confidence: 99%